(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتوقف هذا البحث عند واقع الاقتصاد السوري بالأرقام كما وردت في بعض التقارير. كما أنه يعرض بعض مقومات التنمية في سورية المتمثلة بالمستلزمات المادية والقوى البشرية المؤهلة والخبيرة والاستقرار السياسي، بمقابل ذلك يتوقف عند نقص الاستثمارات وعجز رأس المال الوطني في القطاعين العام والخاص عن الوفاء بحاجة الاستثمار في الاقتصاد السوري، وضيق السوق الداخلية وحالة المواجهة المستمرة كمعوقات أساسية للتنمية في سورية. كما أنه تمت دراسة دور كل قطاع اقتصادي في سورية في عملية التنمية وأي منها يمكن أن يلعب دور قاطرة التنمية, حيث إنَّ الصناعة يمكن أن تلعب هذا الدور إذا ما تم توفير البيئة الملائمة، وتطوير كل قطاع من القطاعات الاقتصادية الأخرى لتعمل على دفع قطاع الصناعة نحو الأمام بدلا من عرقلته. This research studies by number the situation of the Syrian economy as it was mentioned in some reports. It also lists some of the characteristics and of development in Syria to show that the physical, the specialized and experienced human resources, and the political stability are positive aspects, while the lack of investments, the inability of the public and private national capital to fulfill the needs of investment in Syrian economy, the limited inner market, the potential threat of war are of the basic obstacle for development in Syria. There was a study for role of every economic sector in the development process, and which of them will be leading in development, because industry could play this role if the suitable environment was available, and the development of every one of the other economic sectors to move the industrial sector forward instead of hindering it.